Optimalisasi Gizi dan Ekonomi Melalui Pengolahan Produk Fermentasi Berbasis Potensi Lokal, Nata de Coco - Winarno, Winarno; Kusmawati, Wiwik; Sari, Reno Siska; Windriyani, Shinta Masitho (JUPE : Jurnal Pendidikan Mandala, 2023)
One of the community service activities that can be carried out in Mojolangu Village, Lowokwaru District, Malang City by utilizing local potential is processing coconut water which is considered waste by the community into a nutritious product and able to improve the community's economy, namely nata de coco. This extension activity includes three stages, namely: preparation, implementation and evaluation. For Mrs. Siti, as a partner, the assistance provided is training in processing coconut water into nata de coco. The implementation stages of PKM activities are as follows: (a) Program preparation, observation of partner data collection, (b) Survey and planning, (c) Training on processing coconut water into nata de coco. The result achieved through this activity is an increase in public understanding that coconut water can be converted into nata de coco products which have high fiber content and are low in calories.